Cancer Risk of Low Dose Ionizing Radiation - Ali, Yasser F.; Cucinotta, Francis A.; Ning-Ang, Liu; Zhou, Guangming (Frontiers in Physics, 2020)
The construction and operation of synchrotron-generated radiation facilities (SRF) continues to grow, resulting in raising individual’s radiation exposure due to an increased amount of radiation use, e.g., for medical diagnosis and disease treatment, industrial applications, and educational and scientific researches. Space exploration missions and space tourism are additional areas of protracted low dose exposure situations with radiation types not present on the Earth. In contrast to high doses of ionizing radiation, cancer risk of the more commonly encountered or protracted radiation exposure is still under debate and subject to uncertainty. A major challenge lies in providing a scientific basis to estimate low-dose radiation carcinogenesis risks. In this review, we aim through the collected epidemiological and experimental studies’ data to address the central questions in radiological protection; including quantification of the risks and uncertainties from low doses of ionizing radiation and what is a sound scientific consensus to advise on risk perception for low dose radiation exposure.